Identifikasi Bentuk Rekreasi Wisata Bekas Tambang dan Dampaknya Terhadap Petani di Kabupaten Cirebon - Siti Wahana S.P., M.M; Akhmad Jaeroni; Mutia Intan Savitri Herista (Paradigma Agribisnis, 2026)
The transformation of former mining areas into recreational areas is a growing phenomenon in Cirebon Regency in response to landscape changes caused by the natural stone industry. This study aims to identify recreational areas created from former mining areas, their legal status, and analyze their impact on farmers. The study employed a qualitative descriptive method based on secondary data obtained from policy documents, scientific publications, and institutional reports. The results indicate that emerging recreational areas include rock cliff tourism, former mining lakes, and selfie tourism based on ex-mining landscapes, such as in the Batu Lawang and Situ Pajaten areas. Most locations lack formal legal status and still pose potential environmental risks. The impact on farmers is dualistic: providing both an opportunity for income diversification and a source of pressure on agricultural sustainability. These findings demonstrate the importance of integrated agribusiness and tourism management within a sustainable development framework.